Політехнізація шкільної освіти у 1953-1964 рр. (за матеріалами періодичних видань Півдня України) - Грибеник, М.В. (Історичний архів. Наукові студії, 2014)
На основі матеріалів регіональних періодичних видань, проаналізовано досвід політехні-
зації вітчизняної шкільної освіти у 1953-1964 рр. Узагальнені позитивні й негативні
тенденції реформування загальноосвітніх навчальних закладів Півдня України.
Встановлено ступінь взаємодії між пресою та визначеною галуззю. На основе материалов региональных периодических изданий проанализирован опыт
политехнизации отечественного школьного образования в 1953-1964 гг. Обобщены
позитивные и негативные тенденции реформирования общеобразовательных учебных
заведений Юга Украины. Установлена степень взаимодействия между прессой и
указанной отраслью. The current state of historical scholarship increasingly encourage researchers to explore the cultural and spiritual development of the nation. One of the priority sites of national revival takes secondary education – an important part of social progress. Therefore, at the present stage of development of Ukrainian statehood it’s important to determine the best option of development. In this aspect, topical treatment, as well as effective methods failed to national education system. Crudity of solutions, make their decision regardless of public opinion, the real potential of the state that are characteristic of the 50-60's of the twentieth century, largely repeated today. Thus the problem of identification and justification of the main directions and trends in the education system in the years 1953-1964, and its reflection in the pages of magazines, has a scientific theoretical and practical importance. The urgency of this problem is caused primarily by the fact that the historical development of education reflects this southern region specific economic and political life during the period in question. The subject of reforming public education URSR reflected in the works L. D. Berezivska, D. I. Pavlov, J. B. Kukuruzа, L. V. Zaharovskoho, A. I. Yuhno. However, in modern historiography, the analytical researches of periodicals as sources of study polytechnization of secondary education in the South of Ukraine in 50 -60-th of the XX century . The chronological period of the article is from 1953-1964. The beginning of this period is characterized by the liberalization of social life (after the death of Stalin in March 1953) and an attempt to change the model of the Soviet system. The ending is caused by curtailment of education reform in 1958. Based on the relevance of the topic, the author poses the following problem: analyze opportunities reflection periodicals major problems polytechnization in secondary education in the southern region of Ukraine; found in the total amount of newspaper articles material worthy of use in the scientific and historical research.